Best in snow ebook - Rosenfelt, David (Andy Carpenter, 2021)
In this Christmas mystery, lawyer Andy Carpenter and his golden retriever, Tara, are on the beat after a body turns up in the snow and a journalist is the prime suspect. Christmas has come early to the town of Paterson, New Jersey, in the form of a snowstorm that dumps two feet of snow on the ground. Lawyer Andy Carpenter likes snow – white Christmas and all that – but it can cause problems for the walks he takes his dogs on every day. When Andy's golden retriever, Tara, goes to play in the snow and instead discovers a body, Andy ends up on the phone with the local newspaper editor. The murder victim is Mayor Alex Oliva, who had an infamous relationship with the newspaper. Last year a young reporter published an expose, and Oliva had him fired for libel. Now, the young reporter – and prime suspect – is in need of a lawyer. Andy agrees to take the case, though it's not looking good this holiday season. The evidence is piling up faster than the snow in Best in Snow , the next Christmas mystery in the bestselling Andy Carpenter series from David Rosenfelt.